Customer Showrooming Behavior and the Effect on Salesperson Performance - Isabelle Sarah Astari; Juanna Judith Huliselan; Martinus Tjhia Tjen Jong (Universitas Pelita Harapan, 2017)
Indonesia has become the biggest market for e-commerce as it has 250 million inhabitants. Growth of internet and online shopping has made retailers expand their businesses via smartphones. Shopping channels via the internet has given customers another channel to get information and buy products without visiting brick-and-mortar stores. This channel multiplicity potentially leads customers to do showrooming. In this research, showrooming in Indonesia will be explored with sunglasses as the research object and optic salespersons as the research subject. There are 178 samples collected in total for this research with 154 of them being used. Primary data is taken from optic salespersons at a prominent optics store in Jakarta. Partial Least Square (PLS) is used as the data analysis method. The research results show that perceived showrooming behavior has a positive and significant effect on self-efficacy and salesperson performance. Moreover, salesperson self-efficacy also has a positive and significant effect on salesperson performance. Meanwhile, coping and cross-selling strategies have a moderate positive but not a significant effect. These results reflect that salespersons do not respond negatively to customer’s showrooming behavior such as price comparison, window shopping, product information, product availability, and shopping via smartphone in front of the salesperson. Salespersons feel optimistic and confident when customers come because they have been trained for customer orientation, availability of supervisory support, and belief that the customer will do their transaction in brick-and-mortar stores if they give a good explanation about the product.Bahasa Indonesia Abstrak: Indonesia telah menjadi pasar E-Commerce terbesar yang memiliki 250 Juta pengguna pertumbuhan Internet dan online shopping telah menjadikan Retailer berkembang bisnisnya melakui smart phone. Berbelanja melalui saluran Internet telah memberikan pelanggan untuk mendapatkan informasi dan membeli produk-produk tanpa mengunjungi toko secara fisik. Dengan cara ini pelanggan berpotensi untuk melakukan Showrooming. Pada penelitian ini akan diteliti mengenai showrooming di Indonesia Produk yang akan diteliti adalah kaca mata sebagai objek dan tenaga penjual di optik sebagai subjek penelitian. Dari 178 sample yang dikumpulkan untuk penelitian ini hanya 154 yang dapat digunakan, data Primar diambil dari tenaga penjual di toko kaca mata di Jakarta. Hasil penelitian menunjukan bahwa Perceived Showrooming Behavior memiliki pengruh positif dan signifikan, terhadap self efficacy dan Kinerja tenaga penjual. Dan juga Self Efficacy memiliki pengaruh signifikan dan positif terhadap Kinerja tenaga penjual Toko Kacamata, sementara itu Coping dan Cross Selling Strategies memiliki pengaruh yang moderat positif namun tidak berpengaruh signifikan. Hasilnya menunjukan bahwa tenaga penjual tidak menanggapi secara negatif terhadap showrooming yang dilakukan oleh Pelanggan antara lain seperti perbndingan harga, window shooping, informasi produk, ketersediaan barang, berbelanja online didepan tenaga penjual, Tenaga penjual tetap optimis dan percaya diri ketika kedatangan pelanggan karena mereka telah di latih umtuk berorientasi terhadap pelanggan ketersediaanya dukungan dari Supervisi dan percaya bahwa pelanggan akan bertransaksi pada toko fisik apabila mereka menjelaskan dengan baik terhadap produk yang di jual.